Note de recherche. Shipwrecked at Land’s End: The Gaspé Maritime Archaeology Project 2022 Field Season - Kennedy, Carolyn; Dostal, Christopher (Archéologiques, 2023)
Gaspé’s abundant maritime subsistence resources such as whales and cod drew European fishermen for centuries. Exploiting these rich fishing resources required vessels that were well-suited to the challenging geography. These challenges pushed shipwrights to develop new nautical technologies which were implemented in the ships’ construction. The Gaspé Maritime Archaeology Project (GMAP) seeks to study these developing technologies through the archaeological ship remnants in the waters around Gaspé. The 2022 field season pursued this research through a remote-sensing survey of Gaspé Bay and Malbay and by studying a shipwreck on a beach in Cap-des-Rosiers believed to be a 19th-century oceangoing ship.